(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This study investigates the impact of professional mentorship on agricultural development in Cross River State, Nigeria, using a primary data collection methodology. Agriculture remains a critical sector for economic growth and food security in Nigeria, yet its development is hindered by limited access to knowledge, skills, and resources. Professional mentorship, defined as a structured relationship between experienced agricultural experts and farmers, has emerged as a potential strategy to bridge these gaps. The research employed a cross-sectional survey design, collecting data from 300 farmers across three local government areas (LGAs) in Cross River State Calabar South, Odukpani, and Yakurr through structured questionnaires and interviews. Findings reveal that farmers with access to mentorship reported a 35% increase in crop yield, a 28% improvement in income, and enhanced adoption of modern farming techniques compared to those without mentors. Statistical analysis using Pearson’s correlation coefficient (r = 0.68, p < 0.05) confirmed a significant positive relationship between mentorship and agricultural productivity. The study’s theoretical framework, rooted in Social Learning Theory, underscores how observational learning and guidance from mentors enhance farmers’ capabilities. However, challenges such as limited mentor availability and poor infrastructure were identified. The research concludes that professional mentorship significantly boosts agricultural development and recommends policy interventions to formalize mentorship programs, increase funding, and improve rural infrastructure. These findings contribute to the discourse on sustainable agricultural development in developing regions.